2015
DOI: 10.3724/sp.j.1123.2015.07006
|View full text |Cite
|
Sign up to set email alerts
|

Determination of imidaclothiz in tea by QuEChERS cleanup and liquid chromatography-tandem mass spectrometry

Abstract: The method for the determination of imidaclothiz residue in tea by liquid chromatography-tandem mass spectrometry (LC-MS/MS) has been developed. The imidaclothiz in tea was extracted by acetonitrile and purified by QuEChERS with PSA (primary secondary amine), C18, GCB (graphitized carbon black) as the adsorbents. The purified solution was centrifuged and the supernatant was diluted with water of equal volume. The separation was performed on a C18 column with a gradient elution program of acetonitrile (containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…After referring to relevant literature, six extraction solvents including ACN with 0.1% acetate, ACN with 1% acetate, ACN with 2% acetate, ACN with 0.1% formate, and ACN with 1% formate were selected to compare the effects on the extraction of 20 mycotoxins in milk [22], where the analyte retention was applied as an assessment criterion. It is reported that some pH-sensitive mycotoxins could be extracted with acid additives to enhance the effect of combined extraction, as also confirmed in this study [23]. Figure 1 shows that when ACN with 1% acetate was selected as the extractant the recoveries of the 20 mycotoxins ranged from 49.45-94.25%.…”
Section: Optimization Of the Extraction Solutionsupporting
confidence: 80%
“…After referring to relevant literature, six extraction solvents including ACN with 0.1% acetate, ACN with 1% acetate, ACN with 2% acetate, ACN with 0.1% formate, and ACN with 1% formate were selected to compare the effects on the extraction of 20 mycotoxins in milk [22], where the analyte retention was applied as an assessment criterion. It is reported that some pH-sensitive mycotoxins could be extracted with acid additives to enhance the effect of combined extraction, as also confirmed in this study [23]. Figure 1 shows that when ACN with 1% acetate was selected as the extractant the recoveries of the 20 mycotoxins ranged from 49.45-94.25%.…”
Section: Optimization Of the Extraction Solutionsupporting
confidence: 80%
“…Mycotoxin contamination in dark tea has been a topical issue for researchers and consumers in recent years, whether it is the presence of mycotoxins in dark tea affects people's health or the residual mycotoxins having an impact on consumers' health. Many studies have suggested the possibility of mycotoxin contamination in dark tea; aflatoxins (Wu J., 2013;Cui et al, 2020), ochratoxins (Liu et al, 2016;Mo et al, 2016), vomitoxins (Liu et al, 2017;Hu et al, 2019), and citrinins (Li et al, 2020 (Liu et al, 2017) using Quick Easy Cheap Effective Rugged Safe-ultrahigh-performance liquid chromatography-tandem mass spectrometry and OTA was detected in five samples, including two samples of Ripe Pu-erh tea (6.7 and 2.5 μg/kg), one sample of Hunan dark tea (4.0 μg/kg), and two samples of Guangxi Liu Bao tea (0.9 and 1.3 μg/kg). Another more comprehensive survey involving 108 dark tea samples was conducted by Ye et al (2020), which showed that five samples were contaminated by OTA with an average concentration of 0.66 μg/kg and a maximum concentration of 36.4 μg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, OTA at the LOD of 2 μg/kg was not detected in the 20 samples produced between 2016 and 2017 via HPLC–FLD on the basis of IAC cleanup (GB/T 30957–2014, data not shown). Liu et al detected 10 mycotoxins, such as OTA, aflatoxin, and deoxynivalenol, in fermented dark tea. Moreover, the author found mycotoxins in 2 out of 10 samples of Liupao tea with OTA content ranging from 0.9 to 1.3 μg/kg.…”
Section: Discussionmentioning
confidence: 99%